2008
DOI: 10.1583/08-2397.1
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Lower Extremity Distal Embolization Using Embolic Filter Protection:Results of the PROTECT Registry

Abstract: Macroembolization is very frequent in patients undergoing lower extremity interventions, particularly with SilverHawk atherectomy. EFP appears to be very effective in capturing macrodebris, and its use is associated with good acute angiographic outcome. The clinical significance of these findings needs to be determined in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(23 citation statements)
references
References 12 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…Although registry data have suggested that distal embolization is a rather frequent occurrence, its incidence was low in the contemporary nonrandomized DEFINITIVE-LE study. 118 Although no high-quality data are available to guide the use of distal protection for atherectomy, it is often used particularly in the presence of poor or single-vessel distal run-off.…”
Section: Rotational Atherectomymentioning
confidence: 99%
“…Although registry data have suggested that distal embolization is a rather frequent occurrence, its incidence was low in the contemporary nonrandomized DEFINITIVE-LE study. 118 Although no high-quality data are available to guide the use of distal protection for atherectomy, it is often used particularly in the presence of poor or single-vessel distal run-off.…”
Section: Rotational Atherectomymentioning
confidence: 99%
“…Contemporary studies have demonstrated a higher rate of DE in the filter of EPDs (20–58%) [3], [7], [11], or detected by Doppler ultrasound (100%) [8], [12], than angiographically (1%–5%) [1], [2]. The reported incidence of limb-threatening DE during routine lower extremity intervention is 1–2% [1], [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, since these studies did not involve any control groups to confirm the short term or long term clinical efficacy of EPDs, so far it can only demonstrate that certain EPDs are safe and efficient in collecting debris during the procedure. In the Preventing Lower Extremity Distal Embolization Using Embolic Filter Protection (PROTECT) study recruiting 56 lesions treated in 40 patients all with EPDs, a side branch embolization occurred in one patient, and a no-flow phenomenon occurred in another as a result of an overfilled filter [3]. The potential benefit of EPDs must therefore be balanced against the associated complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41,42 A 58-patient RCT of directional atherectomy to PTA in lower extremity PVD showed no difference in initial procedural success or target lesion revascularization (TlR); however, there was significantly more distal embolization with atherectomy. 43 Concern about distal embolization of atheromatous debris has prompted the use of embolic protection devices, 44 and their Food and Drug Administration clearance for use in this setting. Adding the expense of a protection device to the already substantial price of an atherectomy catheter puts equipment cost in the range of $5000, in excess of virtually every other percutaneous strategy.…”
Section: Atherectomymentioning
confidence: 99%